Religious faith and transgender identities: The Dear Abby project. Issue 2 (2nd April 2020) - Ghazzawi, Alhasan; Suhail-Sindhu, Selena; Casoy, Flávio; Libby, Naomi; McIntosh, Christopher A.; Adelson, Stewart; Ashley, Kenneth; Drescher, Jack; Goldenberg, David; Hung, Kenneth; Lothwell, Lorraine E.; Mattson, Marlin R.; et al.
Abstract: Religion and spirituality have been associated in many studies with an impact on mental and physical health. However, the relationship between religious faith and transgender identities is not well studied. To understand this relationship, the LGBT Committee of the Group for the Advancement of Psychiatry undertook a qualitative analysis. Participants in this study are a subset of a larger project investigating the role of religion and spirituality among all members of the LGBTQ community. The larger study invited input on LGBTQ identity and faith using an announcement posted by the "Dear Abby" column, published in hundreds of newspapers around the globe. Of the 86 participants in the study, eight responses were examined by participants who identified as transgender. Qualitative analysis of these survey results revealed the following themes: awareness of gender identity and development, mental health, God's creation and spirit, fear of rejection, ambivalent acceptance, self-sacrifice for community, reconciliation with faith. Themes of both faith identity and gender identity were prevalent. Aspects of dual-identity development were painful and conflictual, but other aspects offered comfort, acceptance, and joy. When a participant's family and community showed even partial acceptance of their transgender identity, greater resilience and integration resulted.